Surgical fixation of the chest wall in traumatic fracture: an integrative review (Jornal Memorial da Medicina, 2022)
This article proposes to carry out an integrative literature review on the different types of chest wall fixation after traumatic fracture and on the indications for such a procedure. There is still no clear consensus on when fixation should be performed or not, since the conservative approach is still widely used and has its advantages and disadvantages, as does the surgical procedure. This study was based on a bibliographic search on the PubMed platform from January to February 2022, using the strategy: (Rib cage) AND (Osteosynthesis) OR (Fracture Fixation, Internal) NOT (Spine) NOT (Cardiovascular Surgical Procedures), resulting in 22 articles, of which 7 were chosen. Most of the selected articles were of a retrospective nature, and also, all of them referred to an approach with early surgical intervention. Early fixation showed pain relief, shorter hospitalization and intubation time, reduced physical limitations, and better range of thoracic motion. Although no consensus was found on all indications, the literature analyzed points to the superiority of surgical fixation of the costal arches in the prevention and reduction of secondary outcomes, such as chest pain and length of hospital stay and mechanical ventilation in patients with respiratory complications is evident,corroborating the indication of this procedure for this group.